Assessment of the potential of temporin peptides from the frog Rana temporaria (Ranidae) as anti‐diabetic agents. (19th January 2018) - Musale, Vishal; Casciaro, Bruno; Mangoni, Maria Luisa; Abdel‐Wahab, Yasser H.A.; Flatt, Peter R.; Conlon, J. Michael
Abstract : Temporin A (FLPLIGRVLSGIL‐NH2 ), temporin F (FLPLIGKVLSGIL‐NH2 ), and temporin G (FFPVIGRILNGIL‐NH2 ), first identified in skin secretions of the frog Rana temporaria, produced concentration‐dependent stimulation of insulin release from BRIN‐BD11 rat clonal β‐cells at concentrations ≥1 nM, without cytotoxicity at concentrations up to 3 μM. Temporin A was the most effective. The mechanism of insulinotropic action did not involve an increase in intracellular Ca 2+ concentrations. Temporins B, C, E, H, and K were either inactive or only weakly active. Temporins A, F, and G also produced a concentration‐dependent stimulation of insulin release from 1.1B4 human‐derived pancreatic β‐cells, with temporin G being the most potent and effective, and from isolated mouse islets. The data indicate that cationicity, hydrophobicity, and the angle subtended by the charged residues in the temporin molecule are important determinants for in vitro insulinotropic activity. Temporin A and F (1 μM), but not temporin G, protected BRIN‐BD11 cells against cytokine‐induced apoptosis ( P < 0.001) and augmented ( P < 0.001) proliferation of the cells to a similar extent as glucagon‐like peptide‐1. Intraperitoneal injection of temporin G (75 nmol/kg body weight) together with a glucose load (18 mmol/kg body weight) in C57BL6 mice improved glucose tolerance with a concomitant increase in insulin secretion whereas temporin A and F administration was without significant effect on plasma glucose levels. The study suggests that combination therapy involving agents developed from the temporin A and G sequences may find application in Type 2 diabetes treatment. Abstract : Temporins A, F, and G produced a concentration‐dependent stimulation of insulin release from clonal β‐cells and isolated mouse islets but only temporin G lowered blood glucose concentrations and stimulated insulin release in mice. Temporins A and F stimulated proliferation of BRIN‐BD11 cells and protected the cells against cytokine‐induced apoptosis.